Leros : A Palimpsest of Confinement - Petsini, Penelope (Design/Arts/Culture, 2025)
This photographic series explores Leros through its layered history of confinement and reform, with a particular focus on the Royal Technical School—a key landmark embodying the island's legacy of control. Captured during a 2017 visit with a National Broadcasting Corporation (ERT) crew, these photographs document restricted and decaying spaces tied to Leros’ complex past, including the Royal Technical School and its surrounding structures. The series investigates the material and symbolic traces of institutionalization, reflecting the island's transformation from an Italian naval base to a re-education camp, psychiatric hospital, and, more recently, a refugee hotspot. Through the lens of photography, the project engages with the physical remnants of confinement, exposing layers of memory and history embedded in the architecture. By transforming these spaces into sites of remembrance, the project challenges viewers to confront the island’s dark legacy while contributing to broader discussions about the intersections of space, memory, and historical consciousness. Leros emerges not only as a physical location but as a palimpsest of trauma and resilience, where confinement and exile continue to inform its identity and collective memory.